Myasthenic syndromes due to defects in COL13A1 and in the N‐linked glycosylation pathway. Issue 1 (24th January 2018) - Beeson, David; Cossins, Judith; Rodriguez‐Cruz, Pedro; Maxwell, Susan; Liu, Wei‐Wei; Palace, Jacqueline
Abstract: The congenital myasthenic syndromes (CMS) are hereditary disorders of neuromuscular transmission. The number of cases recognized, at around 1:100, 000 in the United Kingdom, is increasing with improved diagnosis. The advent of next‐generation sequencing has facilitated the discovery of many genes that harbor CMS‐associated mutations. An emerging group of CMS, characterized by a limb‐girdle pattern of muscle weakness, is caused by mutations in genes that encode proteins involved in the initial steps of the N‐linked glycosylation pathway, which is surprising, since this pathway is found in all mammalian cells. However, mutations in these genes may also give rise to multisystem disorders (congenital disorders of glycosylation) or muscle disorders where the myasthenic symptoms constitute only one component within a wider phenotypic spectrum. We also report a CMS due to mutations in COL13A1, which encodes an extracellular matrix protein that is concentrated at the neuromuscular junction and highlights a role for these extracellular matrix proteins in maintaining synaptic stability that is independent of the AGRN/MuSK clustering pathway. Knowledge about the neuromuscular synapse and the different proteins involved in maintaining its structure as well as function enables us to tailor treatments to the underlying pathogenic mechanisms.